FIRST FINDINGS OF LATE PLEISTOCENE TEPHRAS OF AVACHINSKY VOLCANO (SOUTHERN KAMCHATKA) - Dirksen, O.V.; Bazanova, L.I.; Ponomareva, V.V.; Portnyagin, M.V.; Filosofova, T.M.; Dirksen, V.G. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2024)
In the Nikolaevka-1 quarry (53°05’17.45»N, 158°21’26.28»E), sequence of ash horizons buried in lake sediments formed about 100 thousand years ago were found. Analysis of the composition of volcanic glasses from these tephra allows us to identify for the first time three Late Pleistocene tephras of Avachinsky volcano (21/23, 21/4 and 21/10). In addition, tephra DS7 from one of the centers of the Karymsky volcanic cluster, with an age of about 107 thousand years, was discovered. The stratigraphic position of the Avachainsky volcano tephras, relative this tephra DS7, allows us to state that tephra 21/10 formed slightly less than 100 thousand years ago, while the other two (21/23 and 21/4) are older than 100 thousand years. Estimates of the minimum volumes of material, ejected during these eruptions, make them comparable to most historical eruptive events at this volcano, and the eruption 21/4 — to the most powerful eruption during 20th century, the 1945 eruption.